High-Performance Deep Ultraviolet Photodetector Based on NiO/β-Ga2O3 Heterojunction - Vincent Teng (Nanoscale Research Letters, 2020)
Ultraviolet (UV) photodetector has attracted extensive interests due to its wide-ranging applications from defense technology to optical communications. The use of wide bandgap metal oxide semiconductor materials is of great interest in the development of UV photodetector due to their unique electronic and optical properties. In this work, deep UV photodetector based on NiO/β-Ga2O3 heterojunction was developed and investigated. The β-Ga2O3 layer was prepared by magnetron sputtering and exhibited selective orientation along the family of (2¯¯¯ 01) crystal plane after annealing. The photodetector demonstrated good performance with a high responsivity (R) of 27.43 AW−1 under a 245-nm illumination (27 μWcm−2) and the maximum detectivity (D*) of 3.14 × 1012 cmHz1/2 W−1, which was attributed to the p-NiO/n-β-Ga2O3 heterojunction.